Laws of the State of New York, Comprising the Constitution, and the Acts of the Legislature, since the Revolution, from the First to the Fifteenth Session, Inclusive, at 191, ch. 81, § 1 (vol. II, 1792) - (:unkn) unknown (General Publisher, 1792)
Prohibited storing of gun powder beyond twenty-eight pounds in weight in one location. Violators fined fifty pounds for every "hundred weight" of powder overstocked. Note: The law was passed in 1788, not 1792.
--
Keywords: GUN POWDER STORAGE